(untitled) - Drucker, Peter F. (New York, 1957)
Tells us the United State's economy, politics and government, stage 1945-1989
Keywords: United States,Hoa Kỳ,United States,Hoa Kỳ; Economic conditions,Điều kiện kinh tế,Politics and government,Chính trị và chính quyền; 1945-,1945-,1945-1989,1945-1989; Hoa Kỳ